Sn-doped Zinc Oxide thin films for LPG sensors - R. K. Nath; S. S. Nath; Kumar Sunar (Journal of Analytical Science and Technology, 2012)
Sn doped zinc oxide (ZnO:Sn) thin films have been prepared by chemical spray pyrolysis technique using Zn(CH3COO)2 as a precursor solution and SnCl4 as a doping solution respectively. The dopant concentration (Sn/Zn at%) is varied from 0 to 1.5 at%. The structural, morphological, optical and electrical properties of the films are explored and then tested for LPG sensing. The resistivity of the Sn-doped films decreases with the Sn doping up to 0.5at%, while at a higher doping concentration the disorder produced in the lattice causes an increase in resistivity of the films. Exposure of LPG decreases the resistance of undoped and doped films. The response of the film is measured for both ZnO and ZnO:Sn films at different operating temperature (275-400℃) and concentration (vol %) of LPG in air. It is observed that Sn-doped ZnO films are more sensitive to LPG than undoped ZnO film. In this work, maximum response (~88 %) is observed for 0.5at % ZnO:Sn film for 1 vol% of LPG in air at 300℃. Further all the films have shown faster response and recovery times at higher operating temperatures